That summer - Dessen, Sarah (New York Orchard Books, 1996)
During the summer of her divorced father's remarriage and her sister's wedding, fifteen-year-old Haven comes into her own by letting go of the myths of the past
1
Keywords: Interpersonal relations -- Fiction; Sisters -- Fiction; Weddings -- Fiction